Rahmat dan Bencana dalam Al-Qur’an: Studi Penafsiran terhadap Qs. Al-Ahzab Ayat 17 menurut Buya Hamka - Zainabila, Zainabila; Anwar, M. Ag, Dr. Husnel; Nasution, MA, Dr. Ali Azmi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
There are verses about grace and disaster in the Al-Qur'an, one of which is in QS. Al-Ahzab: 17. But these two words (grace and disaster) many people still misunderstand its meaning. For example, when someone has an amputated hand. Having an amputated hand is poor, but behind this accident, there is grace behind it. If people lack understanding, people will always think badly about what happens. Things like this make the author raise the theme of Grace and Disaster. Hamka with his Al-Azhar Tafsir used as the primary reference. Based on this description, a problem formulation can be taken as follows: How is Hamka's interpretation of grace and disaster in surah Al-Ahzab: 17 in Al-Azhar Tafsir? And what is the relationship between grace and disaster in improving the quality of life in this world and the hereafter? This research is a library research. According to Hamka, the research results obtained from research on grace and disaster in the Al-Qur'an and grace according to Buya Hamka in Al-Azhar Tafsir is a manifestation of God's love for His servants that radiates to charity and deeds until one day he dies with husnul khatimah. Meanwhile, according to Buya Hamka, disasters are divided into two, which are small disasters, such as illness, and major disasters that occur in the universe, such as earthquakes, floods, and volcanic eruptions. Buya Hamka also believes that the disasters was caused by several factors, as mentioned in the Al-Qur'an, which are the factor of human disbelief, the factor of human hypocrisy, and the factor of human disobedience.